Eldercare services in Sweden and the United States - comparative perspective and examples of best practice - Zapędowska-Kling, Kaja (Economics and Business Review, 2014)
The aim of this paper is to discuss the characteristics of the eldercare sector in two considerably different welfare state regimes - Sweden and the United States. In the face of dynamic demographic changes and the ageing of the populations, sectors of care undergo transformation and face new challenges. This article compares and contrasts the American and Swedish eldercare sector, but also brings two examples of best practice selected from the experience of each country. The Programme of All-Inclusive Care for the Elderly is a successful exception in a fragmented and disintegrated landscape of long-term care in the United States. Extended state support for informal carers manifests a new Swedish approach to family care. The paper leads to a conclusion that most of the developed countries need to undertake different actions to prevent a long-term care crisis and prepare the societies for an unprecedented growth of the "oldest old" population.(original abstract)